Tales of justice and rituals of divine embodiment: oral narratives from the central Himalayas - Malik, Aditya (Oxford University Press, 2016)
This work is about ideas of justice in South Asia. It is the result of extensive fieldwork on oral and written narratives, testimonies, and rituals relating to Goludev, the God of Justice, in the Central Himalayan region of Kumaon.
Keywords: Kumaun Himalaya -- Religious life and customs; Gerechtigkeit; Volkserzählung; Religion; Kumauni; Mündliche Überlieferung; Kumaon